Oral immunization with hepatitis B surface antigen expressed in transgenic plants - Kong, Qingxian (The National Academy of Sciences, 2001)
Oral immunogenicity of recombinant hepatitis B surface antigen (HBsAg) derived from yeast (purified product) or in transgenic potatoes (uncooked unprocessed sample) was compared. An oral adjuvant, cholera toxin, was used to increase immune responses. Transgenic plant material containing HBsAg was the superior means of both inducing a primary immune response and priming the mice to respond to a subsequent parenteral injection of HBsAg. Electron microscopy of transgenic plant samples revealed evidence that the HBsAg accumulated intracellularly; we conclude that natural bioencapsulation of the antigen may provide protection from degradation in the digestive tract until plant cell degradation occurs near an immune effector site in the gut. The correlate of protection from hepatitis B virus infection is serum antibody titers induced by vaccination; the protective level in humans is 10 milliunits/ml or greater. Mice fed HBsAg-transgenic potatoes produced HBsAg-specific serum antibodies that exceeded the protective level and, on parenteral boosting, generated a strong long-lasting secondary antibody response. We have also shown the effectiveness of oral delivery by using a parenteral prime-oral boost immunization schedule. The demonstrated success of oral immunization for hepatitis B virus with an “edible vaccine” provides a strategy for contributing a means to achieve global immunization for hepatitis B prevention and eradication.